Simple export of journal citation data to Excel using any reference manager - David Brennan (Journal of the Medical Library Association, 2016)
Working with citation data from literature searches for systematic reviews can be problematic. The quantity of citations can be quite large. Export functions to the various citation managers (e.g., RefWorks, Zotero, Mendeley, EndNote) are not always sufficient to the task.